Disparities in phase 1 cancer clinical trial enrollment. Issue 23 (11th August 2021) - Perni, Subha; Moy, Beverly; Nipp, Ryan D.
Abstract : Background: Phase 1 trials are increasingly important in the molecularly driven era of oncology, but few studies have examined phase 1 participation disparities. The authors of this study investigated factors associated with phase 1 versus phase 2/3 trial enrollment. Methods: They authors conducted a cross‐sectional study using serial samples of patients age ≥18 years enrolling on cancer trials from October 2011 to November 2014 at an academic cancer center. They used univariable and multivariable logistic regression models to analyze sociodemographic and clinical associations with phase 1 versus phase 2/3 trial enrollment. Results: Among 3103 patients enrolled in cancer trials, 2657 unique patients participated in phase 1/2/3 trials. For patients enrolled in phase 1 (n = 1401) versus phase 2/3 (n = 1256) trials, we found no significant differences by age, insurance status, marital status, and income. Overall, 1216 (93%) White, 72 (6%) Asian, and 21 (2%) Black patients enrolled on phase 1 trials, whereas 1068 (93%) White, 40 (3%) Asian, and 43 (4%) Black patients enrolled on phase 2/3 trials. Adjusting for age, sex, race, ethnicity, insurance status, marital status, income, cancer type, disease status, travel distance, and trial year, compared with White patients, Black patients had lower phase 1 enrollment (odds ratio [OR], 0.46; 95% confidence interval [CI], 0.25‐0.82), as did Hispanic/Latino (OR, 0.25; 95% CI, 0.08‐0.79) and male patients (OR, 0.77; 95% CI, 0.62‐0.94). Asian patients had higher phase 1 enrollment (OR, 1.38; 95% CI, 0.88‐2.16). Conclusions: Disparities in phase 1 versus phase 2/3 cancer clinical trial enrollment underscore the urgent need for interventions addressing inequities in early‐phase trial participation. Lay Summary: Phase 1 trials are of increasing importance in oncology. The authors of the study analyzed all patients enrolling on cancer clinical trials at a large academic cancer center from October 2011 to November 2014. Among the 2657 trial participants, when age, sex, race, ethnicity, insurance status, marital status, income, cancer type, disease status, travel distance, and trial year were taken into account, Black, Hispanic/Latino, and male patients were less likely to enroll on phase 1 trials versus phase 2/3 trials. These findings suggest a need for targeted interventions to improve access to and education about phase 1 trials for Black and Hispanic/Latino patients. Abstract : In this cross‐sectional study of 2657 patients participating in clinical trials at a large academic cancer center, Black, Hispanic/Latino, and male patients are significantly associated in multivariable analyses with lower enrollment in phase 1 versus phase 2/3 trials. Age, insurance, marital status, income, and travel distance are not significantly associated with trial enrollment phase.